(untitled) (Medical Forum Monthly, 2024)
Background: Diabetes is a serious metabolic disorder that results in significant morbidity and mortality. Diabetes is characterized by hyperglycaemia resulting in various short-term metabolic changes in lipid and protein metabolism and long-term irreversible vascular changes. Objective: In this study, effect of ascorbic acid on glycation was investigated. Design of Study: Experimental Study. Place of Study: Allied Hospital and National Hospital, Faisalabad. Materials and Methods: Studies were performed by using normal and diabetic plasma. Samples were incubated for 5 weeks at 37 oC temperature and varying concentrations of glucose and vitamin C. Two glycation assays (Thioarbituric acid and Periodate) were used to measure and compare the glycation level. Results: The results indicated that increase in glycation was observed from 1st to 3rd week of incubation and it was decreased after 5th week due to the formation of advanced glycation end products. With three concentrations of ascorbic acid variable responses were observed however, it was observed all three concentrations were responsible to increase glycation. Conclusions: Ascorbic acid will facilitate glycation in hyperglycaemia condition and Periodate borohydride proved itself more reliable and sensitive glycation assays than TBA test.